Analysis of The Relationship Between Profitability and Leverage on Stock Returns in Retail Companies Listed on The Indonesia Stock Exchange (IDX) in 2019–2023 - Mutiara Anggreni Dewi; Wisang Candra Bintari; Mitta Muthia Wangsi; Nur Aeni Waly (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2025)
This study presents an analysis of the effect of profitability ratios and leverage ratios on the stock returns of retail companies listed on the Indonesia Stock Exchange from 2019 to 2023. The purpose of this study is to provide insight into how these financial metrics influence investor decisions and market performance. The findings indicate that both profitability ratios and leverage ratios have a significant impact on stock returns, highlighting the importance of financial health in attracting investment. This research also emphasizes the need for retail companies to adapt to changing market conditions, especially after the COVID-19 pandemic, which forced many retailers to increase their digital presence and operational strategies. This study contributes to the understanding of financial dynamics in the retail sector and is a valuable resource for academics and practitioners in the field of finance.